ATS (Automatic Transfer Switch) Transmission System as Power Supplier for Pahlawan Booster: Sistem Transmisi ATS (Automatic Transfer Switch) Sebagai Penyuplai Daya untuk Booster Pahlawan - Arifin, Nur Rachmad; Dinata, Yusuf Manggala; Pamungkas, Farid Setyo (Procedia of Engineering and Life Science, 2024)
This research aims to investigate the effectiveness of the Automatic Transfer Switch (ATS) system in power transmission by observing and simulating its operation. The results show that the ATS system is highly effective in minimizing downtime during power outages by automatically switching to a backup power source. This discovery has important implications for the management of distributed power networks, particularly in improving responsiveness to power outages. However, the ATS system still has some shortcomings that need to be addressed to avoid potential impacts. Overall, this study highlights the importance of the ATS system in ensuring uninterrupted power supply and the need for further research to improve its performance. Highlight : The ATS system is highly effective in minimizing downtime during power outages. The ATS system has important implications for the management of distributed power networks. Further research is needed to improve the performance of the ATS system Keywords: Automatic Transfer Switch, Power Transmission, Downtime, Backup Power Source, Distributed Power Networks.